Succinate dehydrogenase flavoprotein subunit expression in Saccharomyces cerevisiae--involvement of the mitochondrial FAD transporter, Flx1p. - Giancaspero, T; Wait, R; Boles, E; Barile, M (2008)
The mitochondrial FAD transporter, Flx1p, is a member of the mitochondrial carrier family responsible for FAD transport in Saccharomyces cerevisiae. It has also been suggested that it has a role in maintaining the normal activity of mitochondrial FAD-binding enzymes, including lipoamide dehydrogenase and succinate dehydrogenase flavoprotein subunit Sdh1p. A decrease in the amount of Sdh1p in the flx1Delta mutant strain has been determined here to be due to a post-transcriptional control that involves regulatory sequences located upstream of the SDH1 coding sequence. The SDH1 coding sequence and the regulatory sequences located downstream of the SDH1 coding region, as well as protein import and cofactor attachment, seem to be not involved in the decrease in the amount of protein.